Pronounced Uptake and Metabolism of Organic Substrates by Diatoms Revealed by Pulse-Labeling Metabolomics - Meyer, Nils; Rydzyk, Aljoscha; Pohnert, Georg (Frontiers in Marine Science, 2022)
Diatoms contribute as a dominant group of microalgae to approximately 20% of the global carbon fixation. In the plankton, these photosynthetic algae are exposed to a plethora of metabolites, especially when competing algae are lysed. It is well established that diatoms can take up specific metabolites, such as vitamins, amino acids as nitrogen source, or dimethylsulfoniopropoionate to compensate for changes in water salinity. It is, however, unclear to which extent diatoms take up other organic resources and if these are incorporated into the cell´s metabolism. Here, we explore the general scope of uptake of metabolites from competitors. Using labeled metabolites released during lysis of algae grown under a 13CO2 atmosphere, we show that the cosmopolitan diatom Chaetoceros didymus takes up even dilute organic substrates from these lysates with little bias for molecular weight or polarity. This is reflected by a high degree of labeling in the metabolome of the exposed cells. The newly developed pulse label/ mass spectrometry metabolomics approach reveals that polarity and molecular weight has no detectable influence on uptake efficiency. We also reveal that the taken-up pool of metabolites is partly maintained without metabolic modification within the cells. But also, a substantial part is subject to catabolic and anabolic transformation. One of the most dominant phytoplankton groups has thus has the potential to compete with heterotrophs, suggesting that the observed osmotrophy may substantially impact organic material fluxes in the oceans. Our findings call for the refinement of our understanding of competition in the plankton.